International monetary cooperation, 1945-63 - Tew, Brian (London : Hutchinson University Library, 1963)
This book treats the theory and practice of international monetary cooperation, with special reference to the problems which have arisen since the world war 11, and the institutions which have been developed to meet them.
Includes index.
Includes bibliographical footnotes.
usc 20/08/18
Loans
Keywords: Foreign exchange; Balance of payments; International liquidity; Currency question; Money